Transconjunctival excision of an orbital conjunctival cyst using computer‐assisted 3‐D surgical planning in a dog. Issue 7 (6th July 2021) - Burn, Jessica B.; Komáromy, András M.; Sledge, Dodd G.; Smedley, Rebecca; Coe, Sarah E.; Kim, Sun Young
Abstract: Investigation of exophthalmos and blood‐colored discharge from the left ventral punctum in a dog was consistent with a conjunctival cyst in the orbit. 3‐D prints of the cyst and surrounding facial bones identified a successful transconjunctival approach without an orbitotomy and patency of the left lacrimal duct was reestablished. Abstract : Investigation of exophthalmos and blood‐colored discharge from the left ventral punctum in a dog was consistent with a conjunctival cyst in the orbit. 3‐D prints of the cyst and surrounding facial bones identified a successful transconjunctival approach without an orbitotomy and patency of the left lacrimal duct was reestablished.